1994
DOI: 10.1346/ccmn.1994.0420409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Elemental Mass Balance Methods for Clay Mineral Quantification

Abstract: Abstract--The quantification of the relative mineralogical composition of clay mixtures by powder X-ray diffraction or chemical mass balance methods has been severely hampered by a lack of representative standards. The recent development of elemental mass balance models that do not require standards for all minerals in the mixture may help circumvent this problem. These methods, which are based on the numerical optimization of systems of non-linear equations using the Marquardt algorithm, show promise for mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…During the early and intermediate weathering stages, K may absorb to clay minerals, partially dissolving into water (Nesbitt et al ., ). Aluminum, Mg, Fe, K, Rb, Cs and Ba are mainly elemental components of, or adsorbed on the clay minerals, whereas Na is primarily removed from weathering sites in solution (Nesbitt et al ., ; Harnois, ; Kolka et al ., ; Mermut and Cano, ; Ohta and Arai, ). Copper and Zn could enhance their concentrations in clay minerals relative to parent rocks (Kogel and Lewis, ).…”
Section: Resultsmentioning
confidence: 99%
“…During the early and intermediate weathering stages, K may absorb to clay minerals, partially dissolving into water (Nesbitt et al ., ). Aluminum, Mg, Fe, K, Rb, Cs and Ba are mainly elemental components of, or adsorbed on the clay minerals, whereas Na is primarily removed from weathering sites in solution (Nesbitt et al ., ; Harnois, ; Kolka et al ., ; Mermut and Cano, ; Ohta and Arai, ). Copper and Zn could enhance their concentrations in clay minerals relative to parent rocks (Kogel and Lewis, ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, Kolka et at (1994) demonstrated that a similar non-linear chemical mass balance model could accurately determine the chemistry of two phases (smectite and illite) and mass proportions for three phases (smectite, illite, and halloysite) in 10 artificial mixtures of reference clays. The model used by Kolka et al (1994) was designed to test the accuracy of the non-linear chemical mass balance approach and was not intended for general use with soil or sediment sampies. In this manuscript, we describe a similar nonlinear chemical mass balance model that is designed for quantification of five clay mineral phases commonly found in temperate region soils.…”
Section: Introductionmentioning
confidence: 99%